6-Benzylaminopurine inhibits growth of Monilinia fructicola and induces defense-related mechanism in peach fruit. (15th November 2015) - Zhang, Yangyang; Zeng, Lizhen; Yang, Jiali; Zheng, Xiaodong; Yu, Ting
Highlights: BAP inhibited Monilinia fructicola infection in peach fruit for the first time. BAP could directly suppress Monilinia fructicola growth. BAP could delay fruit senescence and induce host defense against brown rot. BAP exerted little adverse effect on the edible quality of fruit. BAP seems to be a promising alternative to the synthetic fungicides. Abstract: This study demonstrated the inhibitory effect of 6-benzylaminopurine (BAP), the first generation synthetic cytokinin, on the invasion of Monilinia fructicola in peach fruit and the possible mechanism involved for the first time. Our results suggested that BAP treatment had a 63% lower disease incidence and approximately 10 times lower lesion diameter compared to the control throughout the incubation period. In vitro BAP showed a direct inhibitory effect on M. fructicola spore germination. BAP could prevent fruit texture deterioration and protect the cell membrane from oxidative stress, while no adverse effects were observed on fruit quality maintenance. Analysis of defense-related enzymes activities indicated that the use of BAP induced higher specific polyphenol oxidase and peroxidase activities which triggered stronger host defensive responses. Thus, our results verified the proposed mechanism of BAP in controlling M. fructicola by direct inhibitory effect, delay peach senescence and activation of defensive enzymes.